Implicit Analogy in Poem of Imam Shafi'i - Chehama, Aman (Al-Ḍād Journal, 2020)
This paper deals with the implicit analogy in Imam Shafi‘i's poetry. It is one of the most prominent types of analogy in poetry. The desire to know the extent of Shafi‘i elements of poetry. This is done through the descriptive analytical approach. Shafi‘i's poetry, which he designed, was analyzed as an implicit analogy. With a statement of the similarity and the likeness. And to show some of the inherent analogy features of his poems. It comes at the end of this search results: The most important of which are: The implicit analogy is the most prominent analogy in the Imam Shafi‘i poem. Shafi‘i has been used this method to reach his goal and purpose. Especially in persuading an addressee to convey an incident to addressee. He comes with evidence and proofs of his conviction. Shafi‘i's way was used to guide the addressee. Also, he used as a reprimand. The implicit analogy in Imam Shafi‘i's poetry is quite a bit on the artistic style in which the blood of the image takes place. His wings tremble, hovering in the horizons of imagination. The Imam is seen as pouring water into his fertile imagination.